2013
DOI: 10.1108/08858621311330272
|View full text |Cite
|
Sign up to set email alerts
|

A framework for configuring sales support structure

Abstract: Purpose -The aim of this paper is to examine when it is appropriate to provide dedicated support for a sales activity, and in cases where support is desirable, to explore the choice between core team support and external support. Design/methodology/approach -Sales transactions typically require a diverse range of sales activities, including customer contact, scheduling appointments, internal meetings, processing orders, and preparing financing applications. This research develops a framework for understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The second area explores various factors affecting the configuration of sales organizations within the firm (Gessner and Scott, 2009; Rutherford et al , 2014). These studies largely examine sales support systems (Arndt and Harkins, 2013; Moncrief et al , 1986) and the challenges associated with intra-firm relationships (Piercy and Lane, 2003; Speakman and Ryals, 2012). While these studies identify important organizational factors affecting both inside and outside salespeople, we found only one study investigating how organizational structure influences inside sales force capabilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second area explores various factors affecting the configuration of sales organizations within the firm (Gessner and Scott, 2009; Rutherford et al , 2014). These studies largely examine sales support systems (Arndt and Harkins, 2013; Moncrief et al , 1986) and the challenges associated with intra-firm relationships (Piercy and Lane, 2003; Speakman and Ryals, 2012). While these studies identify important organizational factors affecting both inside and outside salespeople, we found only one study investigating how organizational structure influences inside sales force capabilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both practitioners and scholars have reported that the sales environment is changing (Hartmann et al , 2018; Paesbrugghe et al , 2017; Plouffe et al , 2016; Rapp et al , 2017; Arndt and Harkins, 2013; Speakman and Ryals, 2012). Specifically, Hoar (2015) suggests that many sales jobs are headed for irrelevancy, while those that remain need sales methodology overhaul (Narus, 2015).…”
Section: Literature Backgroundmentioning
confidence: 99%
“…The principal aim of any buyer-seller relationship is to increase sales performance and sales performance has been quantified by academia with different measures including higher profit margin, higher total sales, exceeding sales targets, new product sales, long term customer satisfaction, customer retention and new account acquisition (Webber et al, 2018). Arndt and Harkins (2013) defined sales performance as "the timely completion of the activity at a quality which is sufficient for the needs of the buyer and the seller at the lowest reasonable cost" (Arndt and Harkins, 2013, p.434) indicating that sale process is a time-sensitive activity. Stoddard, Clopton, and Avila (2007) also argued that "the sales process efficiency construct includes task outcomes that streamline the sales process (e.g., better time and territory management, enhanced productivity, spending more time with customers, handling more accounts, lower cost of leads, and lower cost of sales)" (Stoddard, Clopton, and Avila, 2007, p.42).…”
Section: Sale Process Efficiencymentioning
confidence: 99%